(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2013)
Introduction: Tuberculosis (TB) is one of the major causes of disease and death in the developing world. World Health Organization recommends that drug resistance surveillance should be carried out regularly in high-burden countries, not only to determine the level of drug resistant TB, but also to strengthen the laboratory capacity. The objective of the study was to evaluate drug susceptibility test (DST) and to observe on DST reports with high variability between the results of two laboratories. Methodology: The study was conducted at Hospital for Chest Diseases and Tuberculosis, SMS Medical College, Jaipur. This was an observational prospective study to analyze DST results, obtained from two different laboratories (Lab A and Lab B), of newly diagnosed sputum positive pulmonary tuberculosis patients registered on DOTS category I. Treatment outcome of patients was obtained from records at the referred clinics and hospitals. Results: Higher proportion of resistance was observed from Lab A (29%) than Lab B (16%), Proportion of MDR strains were higher from Lab A (12.5%) than Lab B (6.0%). Out of the patients whose treatment outcome were available, proportion of patients with treatment success were almost similar in both cohorts (84.6% vs. 85.2%), despite the difference in DST results. Success rate after treatment from Lab A was 60% even in patients with MDR strain, compared to 22% from Lab B. Conclusions: Disparity in DST results was observed from the two laboratories (non accredited and accredited) which does not correlate with the treatment outcome. This study points towards the need of proper quality assurance of the drug sensitivity testing in Mycobacterial testing laboratories. SAARC Journal of Tuberculosis, Lung Diseases & HIV/AIDS; 2013; X(1); 1-6 DOI: http://dx.doi.org/10.3126/saarctb.v10i1.8643